posted by Katie .
How do you solve the rational equation:
I know that the LCD of the equation is (n+2)(n-2) because that is what you get when you factor out the n^2-4 in the last part of the question. I thought I did it right until I reached the end where I don't know how to solve it.
So why not multiply each of the three terms by that LCD that you found to get
n(n+2) + n(n-2) = n
expand and solve as a quadratic.
I factors very nicely and has 2 simple answers.
That's just it. I don't know how to factor it out because i keep getting 2n^2-n=0
2n^2 - n = 0 is correct.
Now take out a common factor
n(2n-1) = 0
n=0 or n = 1/2